The Effect of Capital Structure, Liquidity, and Company Size towards Profitability - Pandapotan, Joy; Lastiningsih, Noegrahini (Journal of Economics and Behavioral Studies, 2020)
This study aims to determine the effect of capital structure, liquidity, and company size on profitability in state-owned companies listed on the Indonesian state-owned enterprise website in 2016 - 2018. This research uses a quantitative approach. This study uses secondary data from company financial and annual report, the sample consists of 65 stated-owned companies. The data analysis technique in this study uses multiple linear regression, classic assumption test, and the hypothesis test consists of the t-test. Based on the results of data analysis known that capital structure has a insignificant negative effect on profitability, liquidity has a significant positive effect on profitability, and company size has a significant negative effect on profitability. The results of this study are expected to be useful for managers in making decisions related to company management, beneficial for investors in choosing investments, and being useful as a reference for further researchers who studying profitability variables